NEW DATA ON THE STRUCTURE AND RADIOMETRIC AGE OF ROCKS OF THE LAPLAND GRANULITE BELT ON THE KANDALAKSHA COAST OF THE WHITE SEA - Sukhanov M.K.; Levitskiy V.I.; Terekhov Y.N. (My University, 1987)
Since the thermoisochron method requires only a small quantity of material (one or a few zircon crystals), the authors able for the first time to date sedimentary rocks and anorthosite that contain only very small quantities of zircon. For this purpose, zircons were extracted from all rock types of the granulite belt except garnet amphibolite, where they were not detected. Also dated were anorthosite and silicic granulite from the area around Lake Yavr in the northern part of this belt, as well as granite-gneiss from the White Sea block near Lake Khannus' yarvi. Study results are discussed.